A critical evaluation of outcomes based education from a developmental perspective in South Africa with particular reference to the Eastern Cape. - Mdikane, Knowledge Mzwandile (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2004)
This research study seeks to examine the impact of Outcomes-Based Education (OBE)from a developmental perspective in the Eastern Cape. Two schools were selected as research sites, one from a previously advantaged area and the other from a previously disadvantaged area. These schools were evaluated on their understanding of OBE and its relationship to development. OBE was introduced in South Africa under controversial circumstances because of the legacy of apartheid education from which we are coming. Because of that, schools in South Africa reflect the inequalities that are resulting from apartheid legislation. In 1994 the government introduced the Reconstruction and Development Programme (RDP) to eradicate all the discrepancies resulting from apartheid. On the educational sphere, OBE was the curriculum policy aimed at eradicating the legacy of apartheid education. The then Minister of Education was convinced that OBE or Curriculum 2005 would be a developmental approach to education and would take South Africa into the 21st century. Ever since its introduction, educators have encountered many problems with the implementation of OBE, especially in the previously disadvantaged areas of the Eastern Cape. The researcher used semi-structured interviews to collect data from the respondents. However, one set of questionnaires was prepared for the educators, students, parents and education government officials. Because of the qualitative nature of the questionnaire the data collected was also analyzed qualitatively. Each question was analyzed from each of the focus groups and the researcher established findings that were analyzed in relation to the literature review. The researcher then was able to reach his own conclusions on the impact that OBE has on the South African education system and recommendations on what could be done for OBE to be successfully implemented and to be developmentally effective in previously disadvantaged areas of South Africa. The recommendations propose useful interventions, which could be made by the government to assist all the stakeholders involved in education in both an understanding and better implementation of OBE in Previously Disadvantaged Areas (PDA's). They include provision of support to stakeholders and that teachers should be taught about the relationship between OBE and reconstruction. The research study focuses mainly on OBE and its relationship to development in urban or Previously Advantaged Areas (PAA's) of two Eastern Cape schools. It will be relevant to the Eastern Cape Education Department in its efforts to implement OBE in schools and it could be a source of knowledge to educators. The conclusion that has been reached, however, is that there is a lot of ignorance about this new system of education to both educators and parents. There is also evidence of ignorance to matters pertaining to the relationship between OBE and it's relationship to the Reconstruction and Development Programme (RDP). A major recommendation that is made then is that for OBE to be relevant in the South African context, it should help to improve the lives of ordinary people in South Africa, especially in Previously Disadvantaged Areas.
Keywords: Reconstruction and Development Programme (South Africa); Competency-based education -- South Africa -- Eastern Cape; Educational change -- South Africa -- Eastern Cape; Education -- Social aspects -- South Africa -- Eastern Cape; Curriculum change -- South Africa -- Eastern Cape